HIV Patients' Satisfaction with Services Provided at Tertiary Health Institutions in Ogun East Senatorial District, Ogun State, Nigeria: Public-private Comparison - Osinaike Abiodun; Ogunkoya John; Sodeinde Kolawole; Abiodun Olumide; Bamidele Fikayo; Adefala Ngozi; Omotosho Y Adebola; Okebalama Victor (Shiraz University of Medical Sciences, 2024)
Background: Patient satisfaction is defined as the extent to which patients feel that their needs and expectations are being met by the services provided. A good number of HIV patients often drop out of treatment programs because they are not satisfied with some aspects of the services provided. This study assessed and compared HIV patients' satisfaction with health services provided at public and privately owned tertiary health institutions in Ogun State, Nigeria.Methods: This is a facility-based 2-center (a government-funded and a privately funded), cross-sectional comparative study carried out among HIV-positive patients who received care at these two tertiary hospitals. HIV patients' satisfaction was assessed using PSQ III. Two hundred patients were recruited from each institution. A comparison of mean satisfaction scores was done using the student's t-test. Logistic regression analysis was used to predict the factors associated with patients' satisfaction.Results: The mean ages of study participants were 42.25±10.81 and 44.04±9.97 for public and private health facilities, respectively (t=-1.717 P=0.087). The mean satisfaction scores of the private health facility (3.48+0.42) were higher compared to those of the public health facility (3.29±0.54) (t=-3.912, P=0.000). Also, more patients in the private health facility were satisfied with the care received compared to the public health facility in six domains out of the seven domains studied.Conclusion: Patients' satisfaction evaluation should be done periodically in health facilities to continually identify the gaps in service delivery and monitor progress towards the ending of HIV/ AIDS epidemics which is one of the targets of the sustainable development goals.